The effectiveness of symbolic formation in children’s theater performances - Ahmed, Ghassan (Al-Adab Journal, 2024)
The current research (the effectiveness of symbolic formation in children’s theater performances) contained four chapters, which the researcher dealt with: The first chapter - the methodological framework of the research, where it included the research problem, its importance, the need for it, its objectives and its limits, and then concluded by defining the terms The second chapter contains the theoretical framework of the research and previous studies, including three topics: The first topic - the researcher dealt with the concept of the symbolic formation of the scene in the theatrical performance. The second topic concerned the effectiveness of the concept of symbolic formation of the scene in theatrical performance by focusing on the historical stages of the scene and its effective symbols in theatrical performance. The third topic dealt with the effectiveness of the concept of symbolic formation of the scene in the children’s theater This chapter concluded with the indicators that the theoretical framework has concluded As for the third chapter: it included the research procedures and the descriptive research methodology, which was formed from the research community, which was limited to the Iraqi theatrical performances presented in (Baghdad - Institute of Fine Arts / Al-Karkh evening). As for the research sample, the researcher deliberately chose his samples. In the fourth chapter, the researcher reviewed the results he had reached, and then the conclusions, recommendations, and suggestions. Among the most prominent findings of the research are: 1- There is an employment of the symbolic formation of the scene clearly in the sample through the use of the symbol to support the dramatic act. 2- Focused on the educational aspect through theoretical formations in conveying the idea. 3- The formations were formed in the landscape and the multiplicity of symbols in clarifying the geometric shapes.